The cyclic nucleotide phosphodiesterase gene of Dictyostelium discoideum contains three promoters specific for growth, aggregation, and late development. - Faure, M (1990)
The cyclic nucleotide phosphodiesterase (phosphodiesterase) plays essential roles throughout the development of Dictyostelium discoideum. It is crucial to cellular aggregation and to postaggregation morphogenesis. The phosphodiesterase gene is transcribed into three mRNAs, containing the same coding sequence connected to different 5' untranslated sequences, that accumulate at different times during the life cycle. A 1.9-kilobase (kb) mRNA is specific for growth, a 2.4-kb mRNA is specific for aggregation, and a 2.2-kb mRNA is specific for late development and is only expressed in prestalk cells. Hybridization of RNA isolated from cells at various stages of development with different upstream regions of the gene indicated separate promoters for each of the three mRNAs. The existence of specific promoters was confirmed by fusing the three putative promoter regions to the chloramphenicol acetyltransferase reporter gene, and the analysis of transformants containing these constructs. The three promoters are scattered within a 4.1-kilobase pair (kbp) region upstream of the initiation codon. The late promoter is proximal to the coding sequence, the growth-specific promoter has an initiation site that is 1.9 kbp upstream of the ATG codon, and the aggregation-specific promoter has an initiation site 3 kbp upstream.